Pengembangan Model Financial Well-Being Melalui Digital Technology dan Green Economy Untuk Sustainable Business IKM Perbatasan - Alexander Mario Retto Djong; Widyaningtyas Widyaningtyas; Hasian Purba; Khenny El Yabes; Aloysius Timothy (Politeknik Ganesha Medan, 2026)
The objectives of this study are: To identify and analyze the level of financial well-being (FWB) of border-based SMEs. To measure the level of Financial Well-Being, digital adoption, green economy adoption, and sustainable business perceptions in a larger and representative sample of SMEs. To statistically test the relationship between variables and confirm/develop qualitative findings. Research Results These results indicate that Financial Well-Being has a positive and significant effect on Sustainable Business through Digital Technology as a mediating variable. Financial Well-Being also has a positive and significant effect on Sustainable Business through Green Economy as a mediating variable. Digital Technology plays a positive role in improving Sustainable Business. Financial Well-Being has a positive and significant effect on Digital Technology. Financial Well-Being contributes positively and significantly in encouraging the development of Green Economy. Financial Well-Being is proven to have a positive and significant effect on Sustainable Business and Green Economy has a positive and significant effect on Sustainable Business.